Ekstrak Minyak Kelapa Daun Gamal (Gliricidia sepium) Sebagai Akarisida Botani untuk Skabies pada Kambing - Sawitri, Dyah Haryuningtyas; Yuningsih, Yuningsih (Jurnal Veteriner; Vol 21 No 4 (2020), 2020)
Scabies is a contagious parasitic skin disease caused by Sarcoptes scabiei . In Indonesia, this disease considerably remains a major problem in animal health, particularly in goats. The aim of this study is to investigate the effectivity of gamal leaves coconut oil extract (GLEC) for scabies treatment in goat. This research was divided into 2 parts: 1. Preparing Gamal Leaves Coconut Oil Extract (GLCE) which included 4 stages of study: collection of gamal leaves; measurement coumarin level in gamal leaves; gamal leaves extraction with coconut oil; and extract stability test and 2. Application of GLCE in goats includes 3 stages of study : artificial S. scabiei infestations in goats; GLCE treatment in goats with 3 concentrations (12.5%, 25%, 50%); and drug safety testing. The results showed that the concentration of coumarin in the gamal leaves which was effectively for scabies drugs was > 1000 ppm. The 12.5%, 25%, 50% of GLCE concentrations are safe as botanical acariside and can reduce 100% of S.scabiei mite populations after 4x, 3x and 2x treatment at 1 week intervals, respectively. The 50% concentration of GLCE is safe, most effective, efficient and stable in storage for scabies drug.